Hubungan Pola Makan Dengan Angka Kejadian Penyakit Karies Gigi Dan Stomatitis Di SD Muhammadiyah 16 Surakarta - Rahmayani, Rahmayani, Arina Maliya , S.kep.,M . S i.,M ed, Endang Zulaicha Susilaningsih, S. K p.,M.Kep (2016)
Occurrences dental caries in Indonesia in 2007 reached 43.4% and increased in 2013 to 53.2%. Occurrences stomatitis in the world reached an average population prevalence of 20%. Based on preliminary research in Muhammadiyah 16 Elementary School Surakarta District. Out of 10 children were in an interview there were 5 children suffering from dental caries due to consume snacks that contains sugar, 2 children suffering from trauma stomatitis by hard objects (collision when brushing teeth), 3 children did not suffer from dental caries and stomatitis. The purpose this research are to determine the relationship of diet and the incidence of dental disease and mouth (stomatitis and dental caries) among children aged 8 to 12 years in Muhammadiyah 16 Elementary School Surakarta District. This research is a quantitative research with cross sectional approach. The population of research which students of Muhammadiyah 16 Elementary School Surakarta Districtamounted to 435 of people. The samples used were 81 respondents to the sampling technique was stratified random of sampling. The instrument used which a questionnaire and checklist. Data analysis used Chi Square test with the results of some of the respondents have enough dietary habit sufficients 40 (49.4%), with the incidence of disease in dental and mouth which most happened one of the (caries or stomatitis) 34 (42%).Results obtained p value 0,001 <α = 0.05. The conclusions, there is a relationship dietary habit with the incidence of dental caries disease and stomatitis in Muhammadiyah 16 Elementary School Surakarta District. Advice are expected of health workers can provide counseling on a good diet so that children avoid the dental and oral diseases in particular (stomatitis and dental caries) so that the child can maintain the health of dental and mouth, especially school children.